QOLP-27. USE OF COMPLEMENTARY AND ALTERNATIVE MEDICINE IN GLIOMA PATIENTS. (5th November 2018) - Hertler, Caroline; Roelcke, Ulrich; Conen, Katrin; Huber, Fabienne; Weiss, Tobias; Hofer, Silvia; Heese, Oliver; Westphal, Manfred; Roth, Patrick; Weller, Michael; Eisele, Günter
Abstract: INTRODUCTION: Beside conventional tumor-specific therapy, glioma patients, as any cancer patients, may seek additional support of complementary and alternative medicine (CAM) treatment during the course of disease. CAM represents a heterogeneous field of agents and treatments, and the use and type may vary from country to country. Despite the existing demand from patients, the use of CAM is neither, by default, incorporated in clinical oncological routine, nor well assessed and documented to date, and little is known about type and motivation for CAM use in specific patient groups. MATERIAL AND METHODS: We conducted a multi-center cross-sectional survey analysis of CAM use in patients suffering from gliomas WHO grades II to IV, treated at specialized Neuro-Oncology Centers in Switzerland in the years 2012–2015. A questionnaire, comprising multiple choice questions as well as open response questions, was handed out to patients on the occasion of an appointment. RESULTS: A total of 208 patients returned the survey, of which 101 patients (49 %) reported the use of CAM, past or present. Of these, 60 were male and 41 female. The main reported motivation for CAM use was the desire to contribute actively to the cancer treatment. CAM use was associated with younger age and was distributed amongst all WHO grades. Usually, CAM use was not supervised by a health care professional, and the costs were not necessarily reimbursed by the insurance company. CONCLUSIONS: In this Swiss multi-center survey analysis, half of the patients harboring a glioma reported CAM use during the course of the disease. Physicians should be aware of this demand and explore CAM use in their patients, to allow for better counseling and avoid potential interactions of CAM with the tumor-specific therapy. Funded by the Swiss Brain Tumor Foundation